CtIP promotes G2/M arrest in etoposide‐treated HCT116 cells in a p53‐independent manner. Issue 7 (27th November 2018) - Chen, Hongyu; Shan, Jin; Chen, Dandan; Wang, Ruoxi; Qi, Wenjing; Wang, Hailong; Ke, Yueshuang; Liu, Wenguang; Zeng, Xianlu
Abstract: Acquired resistance to cytotoxic antineoplastic agents is a major clinical challenge in tumor therapy; however, the mechanisms involved are still poorly understood. In this study, we show that knockdown of CtIP, a corepressor of CtBP, promotes cell proliferation and alleviates G2/M phase arrest in etoposide (Eto)‐treated HCT116 cells. Although the expression of p21 and growth arrest and DNA damage inducible α (GADD45a), which are important targets of p53, was downregulated in CtIP‐deficient HCT116 cells, p53 deletion did not affect G2/M arrest after Eto treatment. In addition, the phosphorylation levels of Ser317 and Ser345 in Chk1 and of Ser216 in CDC25C were lower in CtIP‐deficient HCT116 cells than in control cells after Eto treatment. Our results indicate that CtIP may enhance cell sensitivity to Eto by promoting G2/M phase arrest, mainly through the ATR‐Chk1‐CDC25C pathway rather than the p53‐p21/GADD45a pathway. The expression of CtIP may be a useful biomarker for predicting the drug sensitivity of colorectal cancer cells. Abstract : CtIP can modulate the etoposide sensitivity of HCT116 cells by promoting G2/M phase arrest, which mainly through the ATR‐Chk1‐CDC25C pathway rather than the p53‐p21/GADD45a pathway.